Gestion & Société's approach to cooperation of French firms. Issue 4 (7th October 2014) - Stokes, Peter; Davoine, Eric; Oiry, Ewan; Segal, Jean-Pierre
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to provide a more nuanced image of cooperation in France, first, insisting on the idiosyncratic conditions under which French will be likely to cooperate, and, second, pointing the importance of the local context, finally criticizing the average stereotyped image given by the intercultural management quantitative literature. Design/methodology/approach – The studies behind the article are based on qualitative data and on an interpretative analysis of culture, considered as a frame of meanings through which people read the organizational situation they are in. Findings – Advanced form of cooperation may be obtained when some balance can be established through subtle arrangement between organizational and cultural needs, i.e. allowing staff to escape from their founding fear of servility. Research limitations/implications – Such analysis of the conditions that can facilitate or hinder cooperation should not be limited to France. It may be applied to any other cultural area. Practical implications – Intercultural management training sessions for expatriates could benefit from this qualitative approach. Originality/value – This approach challenges the quantitative main Stream approach in cross-national studies on management.